2019
DOI: 10.1186/s12913-018-3842-y
|View full text |Cite
|
Sign up to set email alerts
|

How do pharmacists in English general practices identify their impact? An exploratory qualitative study of measurement problems

Abstract: BackgroundIn England, there is an ongoing national pilot to expand pharmacists’ presence in general practice. Evaluation of the pilot includes numerical and survey-based Key Performance Indicators (KPIs) and requires pharmacists to electronically record their activities, possibly by using activity codes. At the time of the study (2016), no national evaluation of pharmacists’ impact in this environment had been formally announced. The aim of this qualitative study was to identify problems that English pharmacis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…With clarification of roles and responsibilities that integrate pharmacists within the primary care team, improved information that gives them access to patient notes, and improved communication systems that would come from co-location, it appears that pharmacists could contribute to more effective service delivery, quality and impact, increasing capacity and reducing workload for GPs. 170,171 Thus, potentially, MEMORABLE found some support for the developing role of practice-based pharmacists.…”
Section: Reviewing/reconciling Medications [See Chapter 3 Reviewing/mentioning
confidence: 99%
“…With clarification of roles and responsibilities that integrate pharmacists within the primary care team, improved information that gives them access to patient notes, and improved communication systems that would come from co-location, it appears that pharmacists could contribute to more effective service delivery, quality and impact, increasing capacity and reducing workload for GPs. 170,171 Thus, potentially, MEMORABLE found some support for the developing role of practice-based pharmacists.…”
Section: Reviewing/reconciling Medications [See Chapter 3 Reviewing/mentioning
confidence: 99%
“…The Exeter study noted the potential of a formal, standardised qualification in primary care pharmacy . A small qualitative study in London noted the importance of measuring impact of this new role in pharmacy . However, the Scottish model based on this evaluation and presented below, of a specific competency framework, supported by an IP qualification is an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…[13] A small qualitative study in London noted the importance of measuring impact of this new role in pharmacy. [15] However, the Scottish model based on this evaluation and presented below, of a specific competency framework, supported by an IP qualification is an alternative. In England, all pharmacists have an educational supervisor and a key component of this role was confidence building.…”
Section: Supporting Developing Practicementioning
confidence: 99%
“…Face-to-face focus groups were then conducted with general practice-based pharmacists (from two West London sites) in which participants were asked to discuss which codes on the list might be useful and suggest any other pharmacists’ activities worth considering as coding options. These focus group discussions were audio-recorded, transcribed verbatim and analysed thematically (for detail, see reference [23]). A further 12 codes were generated from the focus group discussions.…”
Section: Methodsmentioning
confidence: 99%
“…Although the evaluation looked at pharmacists’ perceptions about their roles, it made no quantitative measures of their activities. Moreover, a UK qualitative study revealed that the current coding options are not tailored to pharmacists’ work (available coding having pre-dated the ‘pharmacists in general practice’ scheme) and concluded that they are not fit for purpose to effectively identify the spectrum of pharmacists’ tasks within the general practice environment [23]. The purpose, therefore, of this study was to reach a broad consensus amongst experts on what general practice-based pharmacists’ activities should be recorded on the general practice clinical computer systems.…”
Section: Introductionmentioning
confidence: 99%